Fiscal vulnerability and transport infrastructure development in Nigeria - Isiaq O. Oseni; Ibrahim A. Adekunle; Ayomide O. Ogunade (African Governance and Development Institute (AGDI), 2020)
In spite of the massive revenue emanating from oil wealth, the successive government of Nigeria failed to give to its citizenry the dividend of democracy owing in large part to their inability to establish a market clearing situation because of inadequate linkage between the sources and the markets (transport infrastructures). An enquiry into the cause and potential solutions to the problems of transport infrastructure development in Nigeria informed the need to regress indices of fiscal vulnerability on the indicator of transport infrastructure development in Nigeria from 1986 through 2017 using the dynamic ordinary least squares regression technique. Results show that high-levelfiscal vulnerability deters optimal government expenditure on transport infrastructure development in Nigeria. Based on the findings of the study, itis recommended that government should do more to block all leakages of fiscal revenues and subsequently ensure that more allocation is channelled into transporting infrastructure development because of its forward and backward linkages.
Keywords: H5; E44; H12; R4; 330; Fiscal Vulnerability; Transport Infrastructure Development; Nigeria